P-008 Normoglycemia following thrombectomy is associated with improved 90-day favorable outcomes in ischemic stroke patients. (23rd July 2017) - Lucke-Wold, B; Boo, S; Carpenter, J; Tarabishy, A; Rai, A
Abstract : Background: It is well known that hyperglycemia is induced by ischemic stroke and causes detrimental outcomes. Hyperglycemia causes neurons to become stunned with the subsequent arrest of protein synthesis and mitochondrial activity. This arrest can lead to cell death following ischemia. What is unknown however is whether normoglycemia following thrombectomy is protective. We proposed that normoglycemia (blood glucose <125) following thrombectomy would be correlated with improved 90 day outcomes in ischemic stroke patients. Methods: A retrospective cohort study was performed with 187 patients admitted to Ruby Memorial Hospital for acute ischemic stroke and who underwent thrombectomy intervention with or without tPA. Baseline NIHSS and mRS were collected as well diabetes status at time of admission. Glucose levels were recorded within the first 12 hours following thrombectomy. 90 day outcome was grouped into favorable or non-favorable. Analysis was formed by χ 2 analysis and student t-tests with p<0.05 being statistically significant. Results: Normoglycemia following thrombectomy is an independent risk for favorable 90 day outcome χ 2 =10.716, p=0.001. The average blood glucose level within 12 hours following thrombectomy for the favorable outcome group was 117 whereas it was 140 for the poor outcome group (t=3.2, p=0.0017). Interestingly, patients with diabetes were not statistically different than patients without diabetes on 90 day outcome results χ 2 =0.763, p=0.382. 36% of patients with diabetes had favorable outcomes whereas 43.22% of patients without diabetes had favorable outcomes. 91 patients were successfully recanulized and 57.14% had favorable outcomes compared to the 18.87% in the non-recanulized group χ 2 =21.214, p<0.001. Of those patients who had successful recanulization, 41.75% were normoglycemic following thrombectomy. Conclusions: Normoglycemia is an important marker following thrombectomy. If patients have normoglycemia following thrombectomy and recanculization, they are likely to have a favorable long-term course. Hyperglycemia following thrombectomy however is an indication of poor future outcome. Further studies are warranted to elucidate the validity of normoglycemia as a marker for long-term favorable outcome following thrombectomy. Disclosures: B. Lucke-Wold: None. S. Boo: None. J. Carpenter: None. A. Tarabishy: None. A. Rai: None.